An Overview of Deep Learning Methods for Left Ventricle Segmentation - Muhammad Ali Shoaib; Joon Huang Chuah; Raza Ali; Khairunnisa Hasikin; Azira Khalil; Yan Chai Hum; Yee Kai Tee; Samiappan Dhanalakshmi; Khin Wee Lai (Hindawi, 2024)
Indexed by ERA